2022
DOI: 10.1002/nop2.1378
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care units nurses' burnout, organizational commitment, turnover intention and hospital workplace violence: A cross‐sectional study

Abstract: Aims This study aimed to (1) assess the relationship between intensive care unit (ICU) nurses' burnout, organizational commitment and turnover intention, (2) examine the moderating effect of the organizational commitment on the relationship between ICU nurses' burnout and turnover intention, and (3) explore the prevalence and influencing factors of hospital workplace violence among ICU nurses. Design Cross‐sectional study design. Methods Data were collected from August to October 2020 and a convenience sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 112 publications
2
20
1
1
Order By: Relevance
“…The incidence of WPV in this study was lower than that in a survey of Chinese physicians before the COVID-19 pandemic5 38 but higher than that in the same period 11. Turnover intention was also lower than that in pre-COVID-1925 39 and contemporaneous studies 40 41. Given that medical professionals in Beijing have high workloads, the gap between treatment outcomes and patients’ expectations may induce doctor–patient conflicts.…”
Section: Discussioncontrasting
confidence: 58%
“…The incidence of WPV in this study was lower than that in a survey of Chinese physicians before the COVID-19 pandemic5 38 but higher than that in the same period 11. Turnover intention was also lower than that in pre-COVID-1925 39 and contemporaneous studies 40 41. Given that medical professionals in Beijing have high workloads, the gap between treatment outcomes and patients’ expectations may induce doctor–patient conflicts.…”
Section: Discussioncontrasting
confidence: 58%
“…Data acquisition was based on interviews or questionnaires [ 16 , 30 96 ]. Fifty-one studies described the questionnaires [ 31 – 33 , 36 – 44 , 47 70 , 72 80 , 82 , 91 94 ] with the majority using one of the following questionnaires (Workplace Violence Questionnaire [ 97 ] in 14 studies [ 31 , 32 , 36 , 40 , 50 , 52 , 54 , 59 , 64 , 65 , 67 , 72 , 76 , 82 ], the Nursing Incivility Scale [ 98 ] in two studies [ 62 , 96 ], and the Survey of Violence Experienced by Staff [ 99 ] in two studies [ 53 , 70 ]).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…While 18 studies presented data strictly from 12′614 ICU personnel only [ 16 , 17 , 24 , 35 , 44 , 46 , 61 , 63 , 69 , 71 , 73 , 74 , 78 , 79 , 81 , 82 , 88 , 90 ], 57 studies reported data from ICU HCWs as subgroups of larger heterogenic cohorts. Figure 1 presents the categorization of the included studies according to the reported findings.…”
Section: Resultsmentioning
confidence: 99%
“…
Nurse turnover is undeniably having an adverse impact on nurses, patients and organizations (Wang et al, 2023). The turnover of nurses leads to a shortage of nursing resources.
…”
mentioning
confidence: 99%